STUDI EKOLOGI SUMBERDAYA TERIPANG DI NEGERI PORTO PULAU SAPARUA MALUKU TENGAH - Yona Aksa Lewerissa (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Background: Decreasing of sea cucumber resources on numbers and size of fishing capture in Negeri Porto waters influenced its community structures. Further, water environment steadiness will questionable. For this reason, study was done to analyzed community structures of sea cucumbers include of numbers species found, density, potency, species presence frequency, distribute pattern, ecology index and environment measurement. Method: Research done on February to May, 2008 at Negeri Porto used Line Transect Method. Result: showed there were eight species of sea cucumbers found (potency as much as 12.286 individuals). Bohadschia marmorata got highest in numbers species found, density, potency and species presence frequency. There were three distribute pattern of sea cucumbers found wich are uniform, random and group. Conclusion: Sea cucumbers diversity was in lower, species are closed to compatible. B. marmorata and Holothuria edulis are tends to dominate this water. Environment factors such temperature, pH, salinity, DO, turbidity, current and sediment distribute showed that Porto waters was suitable to sea cucumbers growth.